2020
DOI: 10.2807/1560-7917.es.2020.25.39.2001650
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 samples may escape detection because of a single point mutation in the N gene

Abstract: SARS-CoV-2 samples may escape detection because of a single point mutation in the N gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 10 publications
4
143
0
Order By: Relevance
“…An example of a run of the N-gene triplex RT-PCR is shown in Figure S2 . Both laboratory-developed assays were able to reliably detect a SARS-CoV-2-positive patient sample (data not shown) for which a discrepant RT-PCR was reported due to a single mutation in the N-gene [ 18 ]. The N-gene triplex RT-PCR was also tested against a commercial RT-PCR designed for simultaneous detection of N-gene, RdRp-gene and a control.…”
Section: Resultsmentioning
confidence: 99%
“…An example of a run of the N-gene triplex RT-PCR is shown in Figure S2 . Both laboratory-developed assays were able to reliably detect a SARS-CoV-2-positive patient sample (data not shown) for which a discrepant RT-PCR was reported due to a single mutation in the N-gene [ 18 ]. The N-gene triplex RT-PCR was also tested against a commercial RT-PCR designed for simultaneous detection of N-gene, RdRp-gene and a control.…”
Section: Resultsmentioning
confidence: 99%
“…Most available diagnostic tests have limitations and are being continuously subjected to research and development for improving accuracy and precision (Figure 1). 30,42–45 The SARS‐CoV‐2 is rapidly evolving and undergoing mutations, and for ensuring efficacy, the local strains should be sequenced at regular intervals and checked for the mutations that can impact RT‐PCR based diagnosis 46 . Recently, a point mutation has been identified in nucleoprotein gene of SARS‐CoV‐2 which resulted in false negative RT‐PCR test 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ziegler et al. [ 80 ] found that a single nucleotide polymorphism (SNP) in the E gene SARS-CoV-2 from a patient interfered with detection in a widely used RT-PCR assay. Consequently, this underscores the necessity of targeting two independent essential genes of SARS-CoV-2 for reliable detection.…”
Section: Sars-cov-2 Mutations and Consequences On Laboratory Testsmentioning
confidence: 99%
“…Prior to the discovery of the ability of SARS-CoV-2 to be involved in a number of re-infection cases, there have been several notions that individuals who recovered from COVID-19 infection develop immunity and are protected against viral re-infection due to the presence of immunological response by serum neutralising immunoglobulins. The notion which was held by certain governments on the grounds that patients who recovered from COVID-19 were fortified against re-infection and could afford to travel as well as resume work during the pandemic was however, debunked by WHO on the basis of the lack of substantial evidence to confirm the relationship between neutralising antibodies and immunity against re-infection [ 80 ]. Despite this development, several studies have demonstrated that the viral RNA can replicate and diminish in numerical strength in body fluids of convalescent infected individuals for up to 12 weeks [ 81 ].…”
Section: Implications Of Sars-cov-2 Re-infections On Pandemic Controlmentioning
confidence: 99%